2006
DOI: 10.1002/jmri.20780
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MR imaging of pulmonary arteries of normal and experimental emboli in small animals

Abstract: Purpose:To demonstrate the feasibility of pulmonary MRA in living rodents. Materials and Methods:A three-dimensional (3D) gradient echo sequence was adapted to perform a time-of-flight (TOF) angiography of rat lung. Angiogram with a spatial resolution of 195 ϫ 228 ϫ 228 m 3 was acquired in around 33 minutes. The method was then applied in animals before and after pulmonary embolism (PE) induction. Section of the proximal right pulmonary artery was measured and compared between the two populations.Results: Good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Figure 6 displays angiograms measured in systole (25% of cardiac cycle) on the same mouse before and after the injection of beads. Apart from the already observed increase in vessel diameter (see Reference (16) for details) (1.2 vs. 0.8 mm 2 ) there was also a clear slowing down of the incoming blood. The marked decrease in velocity (14 vs.…”
Section: Pulmonary Artery Imagingmentioning
confidence: 64%
“…Figure 6 displays angiograms measured in systole (25% of cardiac cycle) on the same mouse before and after the injection of beads. Apart from the already observed increase in vessel diameter (see Reference (16) for details) (1.2 vs. 0.8 mm 2 ) there was also a clear slowing down of the incoming blood. The marked decrease in velocity (14 vs.…”
Section: Pulmonary Artery Imagingmentioning
confidence: 64%
“…Flow data from the whole lung using MRI may thus provide more global and reproducible information on the impact of chronic hypoxia on pulmonary arteries. In a preliminary study, it was shown that three‐dimensional, bright‐blood, MR angiography (MRA) was useful for the visualization of the main pulmonary arteries in rats 7. It was also possible with time‐resolved angiograms 8 with cardiac and respiratory triggering to measure blood flow velocity in pulmonary arteries at defined steps in the cardiac cycle 9.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast obtained in this study between the vessels and the surrounding tissues (contrast‐to‐noise ratio greater than 11) provided adequate conspicuity of the arterial tree, with the exception of the pulmonary and coronary arteries. Coronary/pulmonary angiography requires specific positioning of double‐oblique oriented volumes (34, 35).…”
Section: Discussionmentioning
confidence: 99%